Developing Capacity Through Networks : Lessons from Anticorruption Parliamentary Coalitions - Campbell, Meaghan (World Bank, Washington, DC, 2012)
National, regional, or global networks of parliamentarians are proving important vehicles for enhancing their capacity and the effectiveness of parliaments and parliamentarians in developing countries. The networks have been particularly active in fighting corruption and mitigating its negative impacts on economic and human development. This Capacity Development (CD) Brief reviews the activities of several such networks worldwide at the individual, regional, and global levels that are making a difference in the ability of parliamentarians to address corruption in their countries.